Compreendendo o grupo BRICS na sua trajetória: condições sistêmicas e composição de interesses - Medeiros, Klei Pando (2021)
This thesis aims to understand, characterize and analyze the trajectory of the BRICS (Brazil, Russia, India, China and South Africa) group. It is argued that the group has a dynamic character and has changed its performance based on the systemic conditions and its composition of interests, with greater convergence and accommodation or divergence and conflict among its member countries. Therefore, three periods in the BRICS trajectory stand out. Between 2006 and 2010, the arrangement gradually became institutionalized and built a common agenda centered on the economic and financial area. The 2008 global economic crisis and a systemic scenario that indicated the rise of emerging countries and the relative decline of the US and Europe stimulated the BRICs' actions in favor of reforms in traditional economic institutions - such as the IMF and the World Bank (WB) - and the elevation of the G-20F to the main forum of global economic governance. The BRICs also coordinated positions in the crisis management. Between 2011 and 2014, the Arab Spring and its geopolitical developments prompted an expansion of the group's security agenda, including attempts at coordination at the UN Security Council. However, there were several differences between the BRICS on the conflicts in Libya, Syria and Ukraine. Therefore, in this period, the creation of the New Development Bank and the Contingent Arrangement of Reserves, which would be administered by the five countries, stood out. Building their own financial institutions is associated with a greater convergence of governments in this area and with restrictions in the traditional multilateral financial system, including the delay in implementation and the insufficiency of the 2010 reforms agreed at the IMF and the WB. Between 2014 and 2020, three important changes took place, with impacts on the group's performance: 1) changes in political forces in power in India (2014), Brazil (2016) and South Africa (2018) and economic and political crises in the last two; 2) growing dispute between India and China and crisis in the Brazil-China relationship; 3) systemic conditions marked by tensions between the great powers, the return of geopolitics, the crisis of multilateralism and the rapid rise of China. These changes resulted in a period of lesser impetusfor the group. In short, the BRICS must be understood as a dynamic arrangement, which modifies its performance based on both systemic conditions and its composition of interests